A SYBR® Green-based real-time PCR method for improved detection of mcr-1-mediated colistin resistance in human stool samples. (June 2017) - Donà, Valentina; Bernasconi, Odette J.; Kasraian, Sara; Tinguely, Regula; Endimiani, Andrea
Highlights: A SYBR ® Green-based real-time (rt)-PCR for mcr-1 detection in faecal specimens was designed. The method was unable to detect all native stools with mcr-1 -positive strains. 100% sensitivity was obtained testing stools enriched in LB broth containing colistin. The rt-PCR also assures concomitant isolation of mcr-1 -harboring strains. This approach represents valuable information for other developed mcr-1 rt-PCRs. Abstract: Objectives: The aim of this study was to design a rapid and sensitive real-time PCR (rt-PCR) method for colistin resistance mcr-1 gene detection in human faecal samples. Methods: Stools ( n = 88) from 36 volunteers were analysed. To isolate mcr-1 -producing Enterobacteriaceae, samples were enriched overnight in Luria–Bertani (LB) broth containing 2 mg/L colistin and were then plated on selective agar plates with 4 mg/L colistin. A SYBR ® Green-based rt-PCR targeting mcr-1 was then designed. For method validation and to establish the limit of detection (LOD), total DNA was extracted from mcr-1 -negative and mcr-1 -positive Escherichia coli . rt-PCR was also performed with DNA extracted from 88 native stools and after enriching them in LB broth containing colistin. Results: Based on the culture approach, three unique volunteers resulted colonised with mcr-1 -harboring E. coli strains. For culture isolates, rt-PCR exhibited a LOD of 10 genomic copies/reaction, with both sensitivity and specificity of 100%. Nevertheless, when testing native stools, only two of the three mcr-1 -positive specimens were detected. However, after enrichment in LB broth containing colistin, the rt-PCR was strongly positive for all culture-positive samples. The average cycle threshold was 22, granting rapid and confident detection of positive specimens within 30 cycles. No false positives were observed for the remaining 85 culture-negative specimens. Conclusions: A rapid rt-PCR for detection of mcr-1 from stool specimens was developed. The detection rate was increased by testing selective broth enrichments. This approach also has the advantage of concomitant isolation of mcr-1 -harboring strains for further antimicrobial susceptibility and genetic testing.